PENGARUH KEBIJAKAN DIVIDEN, UKURAN PERUSAHAAN, DAN FAKTOR LAINNYA TERHADAP NILAI PERUSAHAAN - Umar Issa Zubaidi; Lorenzo Hansen (E-Jurnal Akuntansi TSM, 2022)
This study is aimed to provide empirical evidence about influence of dividend policy, firm size, company productivity, board size, board independence, size of audit comitee, profitability, and capital structure on firm value. Firm value can be maximized by knowing factors that can affect firm value. This study uses secondary data which is the financial statement and annual report data from non-financial company for the period 2017 to 2019 which are listed on the Indonesia Stock Exchange (IDX). The sample selected in this study has been determined by purposive sampling method. Total sample used in this study is 126 companies. Analysis technique of data used in this study is multiple regression analysis. Results of the study indicates that dividend policy, company productivity, board size, profitability and capital structure have significant effect on firm value.